PENGARUH MOTIVASI KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Perusahaan Nety Collection di Malang) - Umama, Hanny Azza (Sains Manajemen, 2016)
Hany Azza Umama, Post Graduate Program of Brawijaya University Malang, Mei, 2006. Work Motivation and Work Ability Impact on Employee Performance (Case Study in Nety Collection Company in Poncokusumo, Kabupaten Malang).Employee performance inan interesting topic and need a constant reexamination since company performance depends on employeeperformance in the company.The research aim in to examine the impact of work motivation and work ability on employee performance. The result is expectedto give a broader knowledge on human resources management and as reference for further research.Multiple Regression Analysis was used to analysis the dataset. The research use all employee of Nety Collection Company in Poncokusumo. F-test was applied to test independent variablesâimpact on dependent variable simultaneously. And t-test was applied to test independent variablesâ impact on dependent variable partially.The result shows that the need of existence, relation, growth, physical ability, intellectual ability, emotional and spiritual ability together have significant effect on employee performance. Among all those variable, the need of existence, growth,intellectual ability, emotional and spiritual ability have effect on employee performance partially. On the contrary, the need of relation and physical ability have no significant effect on employee performance. Variable with biggest effect is the need of growth.In order to increase employeâs performance, the company should fulfill the need of existence and growth, increase intellectual ability, emotional ability, and spiritual ability.But most important thing in fulfilling the need of growth because it has the biggest effect on employeeâs performance.